(3x+4)(2-5x)=0

Simple and best practice solution for (3x+4)(2-5x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+4)(2-5x)=0 equation:


Simplifying
(3x + 4)(2 + -5x) = 0

Reorder the terms:
(4 + 3x)(2 + -5x) = 0

Multiply (4 + 3x) * (2 + -5x)
(4(2 + -5x) + 3x * (2 + -5x)) = 0
((2 * 4 + -5x * 4) + 3x * (2 + -5x)) = 0
((8 + -20x) + 3x * (2 + -5x)) = 0
(8 + -20x + (2 * 3x + -5x * 3x)) = 0
(8 + -20x + (6x + -15x2)) = 0

Combine like terms: -20x + 6x = -14x
(8 + -14x + -15x2) = 0

Solving
8 + -14x + -15x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(2 + -5x)(4 + 3x) = 0

Subproblem 1

Set the factor '(2 + -5x)' equal to zero and attempt to solve: Simplifying 2 + -5x = 0 Solving 2 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -5x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -5x = 0 + -2 -5x = 0 + -2 Combine like terms: 0 + -2 = -2 -5x = -2 Divide each side by '-5'. x = 0.4 Simplifying x = 0.4

Subproblem 2

Set the factor '(4 + 3x)' equal to zero and attempt to solve: Simplifying 4 + 3x = 0 Solving 4 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 3x = 0 + -4 3x = 0 + -4 Combine like terms: 0 + -4 = -4 3x = -4 Divide each side by '3'. x = -1.333333333 Simplifying x = -1.333333333

Solution

x = {0.4, -1.333333333}

See similar equations:

| c=(2)(3.14)(r) | | 9x-4y=-2 | | 6.3y=4.1y+12 | | 1.2=1.6m | | c=23 | | -8=5a-3a | | -54=133.578499968x+0.5*0.0209625668*17843.21565 | | 6(x+2)-(3x-8)= | | 4(x+3)-(2x-4)= | | 54=133.578499968x+0.5*0.0209625668*17843.21565 | | 3b+(4b-6b+2)-b=10 | | 13t^2-10t+2=0 | | 11t-8t=-3 | | 11=x-(-9) | | 7*x-2=0 | | x(2)+3=x | | -9(12)*15(145)+4b=3 | | 4m-8n-7m=0 | | a-10=-16 | | 5z-3=17 | | 7a^2-64a+64=0 | | x^2=7.84+2*0.0209625668*133 | | 0=ln(x-5) | | 3(p-4)=36 | | 5m^2-42m+49=0 | | 9x+12-8x=-6+(-4) | | 96-7x=29x+20 | | 320=187+133.578499968x+0.5*-0.0209625668*17843.21565 | | k-273.15=c | | -x+8x=-38-4 | | 9-10x=145-38x | | X^5+3x^4-189x^3+797x^2-612x=0 |

Equations solver categories